The influence of compression molding processing parameters on the mechanical properties of a cellulose fibre composite - Danielsson, Niklas (My University, 2017)
Core innovation has developed a new isostatic compression method to manufacture 3D shaped objects from fluffed pulp. However, detailed knowledge is needed about the influence of manufacturing parameters on the mechanical properties of the composite. The goal of the project was to study three manufacturing parameters, pressure, temperature and compression time, and their effect on mechanical properties of the final product. Further, an investigation for possible use of the material was conducted. Commercial fluffed pulp was formed into a air-laid fibrous mat, compression moulded under various manufacturing conditions and lasercut to produce dog bone shaped specimen. The final composite showed a plastic-like surface and mechanical properties(as Young's modulus and Ultimate tensile strength) similar to common plastics based on petroleum. Specimen with higher densities after compression showed better mechanical properties. The pressure yielded higher density specimen. The temperature during compression moulding gave very small results in Young's modulus. A higher temperature showed a slight tendency towards more brittle material and a brown/yellow discoloring. It was also showed that the difference of compressing the material for 3 seconds and 30 seconds was very small. That eases the industralization of the new material as short cycle times are preferred.
Keywords: Materialteknik; Materials Engineering